2017
DOI: 10.5740/jaoacint.16-0412
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Edible Oils Based on ATR-FTIR Spectral Information During a Long Heating Treatment

Abstract: Identification of oil type and its QC are important concerns in food control laboratories. Classifying edible oils that have not been used (i.e., unheated) with the aid of vibrational spectroscopy has previously been reported. However, the classification of used (i.e., heat-treated) oils needs special attention. The effect of long heating times on the classification of four kinds of edible oils (canola, corn, frying, and sunflower) based on attenuated total reflectance (ATR)-FTIR spectra was surveyed. The samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The accuracy shows the ratio of the correct number of assessments to the number of all assessments. If all of the samples of a class are correctly recognised (true assigned), a sensitivity value is equal to 1 is obtained and if the samples do not belong to a class, they are never assigned to that class (true not‐assigned), specificity is equal to 1 37 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The accuracy shows the ratio of the correct number of assessments to the number of all assessments. If all of the samples of a class are correctly recognised (true assigned), a sensitivity value is equal to 1 is obtained and if the samples do not belong to a class, they are never assigned to that class (true not‐assigned), specificity is equal to 1 37 …”
Section: Resultsmentioning
confidence: 99%
“…The specificity shows the number of true‐negative assessment portion in all negative assessments and measures how well the model can predict samples from the control class, while the sensitivity is a fraction of the number of true‐positive assessment to all positive assessments and describes how well the model is capable to correctly classify the samples of each class. The accuracy is another metric that shows the ratio of the correct number of assessments to the number of total assessments 37,38 …”
Section: Methodsmentioning
confidence: 99%
“…ATR-FTIR spectroscopy is an effective and sensitive method for edible oil classification. It has been successfully exploited to monitor the molecular changes in terms of dominant functional groups occurring in severely oxidized oils 26 . The ATR-FTIR spectrum of Mann-S1 is compared to that of authentic EVOO in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the combination of ATR-FTIR spectroscopy and chemometrics was effective in distinguishing between these oils. Another example is the classification of edible oils based on ATR-FTIR spectral information during a long heating treatment . This study used a combination of ATR-FTIR spectroscopy and chemometrics to monitor the changes in the chemical composition of different edible oils during heating.…”
Section: Introductionmentioning
confidence: 99%
“…Another example is the classification of edible oils based on ATR-FTIR spectral information during a long heating treatment. 19 This study used a combination of ATR-FTIR spectroscopy and chemometrics to monitor the changes in the chemical composition of different edible oils during heating. The results showed that the ATR-FTIR spectroscopy and chemometrics approach was effective in detecting changes in the chemical composition of the oils during heating.…”
Section: Introductionmentioning
confidence: 99%